Implementation of Differentiated Instruction in Mathematics Learning to Increase Student Engagement at SMAN 1 Indramayu - Rahmatulloh, Rahmatulloh; Alfin, Edward; Supriyatno, Dawud; Natalia, Desi; Nurfatah, Agus; Setyawati, Nunuk; Nugroho, Erwin Raka (Universitas Wiralodra, 2026)
This study examines the implementation of differentiated instruction in mathematics learning at SMAN 1 Indramayu, focusing on how teachers design and apply differentiation in terms of content, process, and product, as well as its impact on student engagement. A qualitative descriptive exploratory approach was employed. Data were collected through classroom observations, semi-structured interviews with teachers and students, and document analysis of lesson plans and learning materials. The data were analyzed using an interactive qualitative analysis model involving data reduction, data display, and conclusion drawing, supported by triangulation across data sources to ensure credibility. The findings indicate that teachers successfully implemented differentiated instruction, particularly by adapting learning processes and products to students’ readiness levels and interests. This implementation led to increased student engagement across behavioral, emotional, and cognitive dimensions. Behavioral engagement improved through more active classroom participation, emotional engagement increased as students showed greater enthusiasm and enjoyment, and cognitive engagement strengthened as students demonstrated improved problem-solving and analytical abilities. Additionally, differentiated instruction promoted inclusivity and collaboration, aligning with the objectives of the Merdeka Curriculum. Despite challenges such as limited preparation time and technological constraints, differentiated instruction proved effective in enhancing classroom dynamics and learning outcomes. Continuous professional development and institutional support are recommended to sustain its implementation in mathematics education.